Refleksi nilai kemanusiaan pancasila dalam perlindungan hak digital di era media sosial - syifa, Masyitah nahda (Maliki Interdisciplinary Journal, 2025)
The issue of digital rights protection is becoming increasingly crucial in the rapidly evolving social media era. This study aims to analyze the reflection of the value of Just and Civilized Humanity, one of the principles of Pancasila, in the context of digital rights protection in Indonesia. Pancasila serves as the source of national legal values, underpinning the formation and interpretation of the entire legal system. Digital rights are understood as an expansion of existing Human Rights (HAM), encompassing the right to privacy, data control, freedom of expression, digital access and literacy, and the right to economic benefits from digital activities. The implementation of this protection faces significant challenges, primarily due to low levels of digital literacy among the public and technical complexities such as cross-border jurisdiction and the anonymity of cyber criminals. Therefore, a holistic approach is necessary, combining regulatory reform (such as the ITE Law), strengthening institutional capacity, and public education on internet ethics and responsibility from an early age, ensuring that Pancasila’s values are internalized and realized in a fair, secure, and sustainable digital ecosystem.